PRODUCT LAYOUT IMPROVEMENT FOR FORWARD WAREHOUSE OF PT X AT LOCATION Y BY MINIMIZING PICKERâS EXPECTED TRAVEL DISTANCE ON ORDER PICKING ACTIVITY - AMATURRAHMAN DALIMUNTHE, AFIYAH
The increasing potential in e-commerce business demands every player in the sector to strive for excellence and improve their performance. PT X is a limited liability company that has recently penetrated into the O2O business field, which is a business that uses the concept of e-commerce to mediate manufacturers with retails such as stalls or traditional grocery stores. Until now, PT X still manages to fulfil orders from the retails with their current resources. However, as orders increase from time to time, the company must improve their efficiency in order to keep serving their customers. A critical activity that is considered to provide the most significant efficiency improvement for PT X’s business activities is the order-picking activity. In this research, product layout design for PT X’s forward warehouse in location Y is done to increase the efficiency of order-picking activity. In the existing condition, more than a thousand different types of product are stored randomly without a dedicated location for each type of product. The proposed design is obtained by using an optimal product layout design method which is able to minimize picker’s travel distance expectation when performing order-picking based on proven mathematic theorem. This method determines storage location for each product group based on its order probability. Product group with the largest order probability is assigned to the nearest storage location from the input/output point, hence product group with the smallest order probability is assigned to the farthest storage location from the input/output point. After the proposed layout is obtained, a calculation is performed to determine the picker’s travel distance expectation based on existing and proposed layouts. A decrease in picker’s travel distance expectation is estimated to occur as much as 59.38% for food category and 57.32% for non-food category.